Between two worlds : Jean Price-Mars, Haiti, and Africa - Joseph, Celucien L.; Saint Paul, Jean Eddy; Mézilas, Glodel (Black diasporic worlds., 2018)
This work explores the contributions of Jean Price-Mars to Haitian history and culture and interprets his connections with Black internationalism, Harlem Renaissance, and the Negritude movement. The book also underscores Price-Mars's contributions to post colonialism, religious studies, Africana studies, and pan-Africanism.